Redox-driven restructuring of lithium molybdenum oxide nanoclusters boosts the selective oxidation of methane. (April 2021) - Kim, Younhwa; Kim, Tae Yong; Song, Chyan Kyung; Lee, Kyung Rok; Bae, Seongjun; Park, Hongseok; Yun, Danim; Yun, Yang Sik; Nam, Inho; Park, Jungwon; Lee, Hyunjoo; Yi, Jongheop
Abstract: Selective methane oxidation is one of the key challenges in modern chemistry. To increase the value-added chemical production, the oxidation state of active metals should be easily converted to oxidized or reduced states in order to adsorb or provide an oxygen atom efficiently into methane. Here, we firstly report that lithium incorporating molybdenum oxide with silica supports significantly enhances HCHO production in virtue of redox-driven restructuring of active molybdenum sites. In reduction conditions under CH4 flow, lithium ions are inserted into the molybdenum-oxide phase by forming lithium molybdenum oxide (Liy MoO3 ) nanoclusters and conversely extracted by O2 oxidation. Due to the redox migration of lithium ions and reconstruction of Liy MoO3 nanoclusters under the reaction process, the oxidation state of active molybdenum centers is effectively controlled to both oxidized and reduced states. These findings provide insight into the distinct role of lithium ions in various catalytic systems and suggest new strategies for developing active sites for selective oxidation area. Graphical Abstract: ga1 Highlights: 0.7Li-MoOx /SiO2 catalyst shows maximum HCHO production, sustaining the excellent level of HCHO selectivity. Li ions are inserted into MoOx phase under reductive conditions (H2 or CH4 ) and extracted under oxidative conditions (O2 ). The Mo oxidation state is controlled to both oxidized and reduced state by migration of Li ions during methane oxidation. The redox-driven restructuring of Liy MoO3 nanoclusters lowers the free-energy barrier of CH4 and O2 conversion steps.